Development of digital based infographic and interactive timeline media for the daulah abbasiyahtopic at SMP IT Harapan Umat Karawang - Diah Iskamtini; Indrya Mulyaningsih; Zaenal Masduqi; Cahya Edi Setyawan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study developed and evaluated a web-based learning medium combining infographics and an interactive timeline for teaching the Abbasid Caliphate (Daulah Abbasiyah) in Grade 8 Islamic Cultural History (SKI) at SMP IT Harapan Umat Karawang. Using the ADDIE research and development framework, the product was created through needs analysis, design, development, implementation, and evaluation. Feasibility was assessed through expert validation of content and media quality, followed by revisions to ensure instructional accuracy and usability. Effectiveness was examined through paired pretest–posttest measures across five parallel classes (A–E), supported by descriptive statistics, paired difference testing, and effect size reporting. Student perceptions were also captured through a questionnaire to document acceptance and perceived usefulness of the media. The findings indicate that the developed media is highly feasible and positively received by students, and overall learning outcomes improved after the intervention, although gains varied across classes. These results suggest that chronology-oriented digital media can support learning of complex historical content, but its impact depends on classroom context and how the media is orchestrated within instructional activities.